Characterization of Self-Regulation of Learning as an Executive Function in Students Within Virtual Learning Environments - Vega Galván, Dannia Narey; Carrillo Maza, Luisa Fernanda; Paez-Manjarrez, Patricia; Ron-Grajales, Arturo; Maldonado-Torres, Francisco Antonio (My University, 2025)
Virtual Learning Environments (VLE) are part of the academic offerings of higher education institutions, defined as the space created through information and communication technologies where a series of environments converge to facilitate analysis, reflection, and appropriation of knowledge (Ramírez García et al, 2021). In these environments, self-regulation of learning is relevant for satisfactory academic performance. Self-regulation is a process by which students control their thoughts, actions, and emotions to achieve specific learning goals (Zimmerman et al., 1996). Executive functions are cognitive skills that allow planning, organization, decision-making, and impulse control, which are fundamental for effective self-regulation (Barkley, 2012). The purpose of this study is to characterize the profile of self-regulation, as an executive function, in graduate students and executive careers participating in Virtual distance education at a university located in northwestern Mexico. The project was developed following a non-experimental methodology, a quantitative approach, correlational and cross-sectional scope. Two assessment instruments were used: the Behavior Rating Inventory of Executive Function, Self-Report (BRIEF-A) and the Motivated Strategies for Learning Questionnaire (MSLQ). This paper presents the results of the first of two phases, which consisted of a pilot test of the BRIEF-A instrument with 71 students, obtaining relevant information on executive functions related to planning, organization, self-monitoring and metacognition.
Conference: BCE2024 (This paper is part of the BCE2024 Conference)
Keywords: Self-Regulation; Online Learning; Executive Functions; Higher Education; Campus Ensenada